Roman Frontier Archaeology - in Britain and Beyond Papers in Honour of Paul Bidwell Presented on the Occasion of the 30th Annual Conference of the Arbeia Society - Hodgson, Nick; Griffiths, Bill (2023)
Roman Frontier Archaeology - in Britain and beyond gathers contributions by some 30 leading archaeologists and historians in honour of Paul Bidwell. In a wide-ranging career Paul has been one of the leading excavators and pottery specialists of his generation, admired for his ground-breaking work both in the south-west and the military north of Roman Britain.Contributions reflect the wide range of Paul Bidwell's interests. Studies of samian pottery use, coins, carved stone pinecones, multi-piece bone dice and agricultural strategies shed light on the economy and everyday life of a Roman frontier province. For the civil southern part of the province there are studies of place-names and various aspects of the public baths of the Roman cities, as well as the impact of changing sea-levels on coastal topography. A number of contributions focus on the problems of the military north and Hadrian's Wall, including studies of the nineteenth century antiquarian pioneers and assessments of the purpose of the Wall, the possibility of destructive attacks by an enemy, the way in which Roman forts were designed, and the use of Iron Age tradition military gear by the Roman army. The papers also take us beyond Britannia to consider developments on and beyond Rome's Eastern, Danube and North African frontiers. The collection will be essential reading for anyone with an interest in either the civil or military aspects of Roman Britain, or the frontiers of the Roman empire.Paul Bidwell (1949-2022)Tragically Paul Bidwell died after a short illness in November 2022 soon after being presented with this book by his friends and colleagues. What was conceived as a gesture to honour Paul has become, in effect, a monument to one of the most respected Roman archaeologists of his generation, and a testament to the wide range of his archaeological interests and achievements.